2015
DOI: 10.1210/en.2015-1403
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution and Neuropsychological Development: A Review of the Latest Evidence

Abstract: For the last decade, literature on the detrimental impacts of air pollution on brain, cognition and behavior has exponentially increased. Our aim is to review the latest epidemiologic literature on the association between outdoor air pollution and neuropsychological developmental in children. Two independent researchers searched for published studies between January 1, 2012 and June 12, 2015 in MEDLINE, Web of Science, and Science direct using defined keywords on outdoor air pollution and neuropsychological de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
167
4
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 245 publications
(179 citation statements)
references
References 52 publications
3
167
4
3
Order By: Relevance
“…To date, we lack a clear understanding of the causes of ASD despite its serious social impact. Based on the most recent reviews of the role of environmental toxicants in the etiology of ASD (e.g., Rossignol, Genuis & Frye, 2014; Suades-González, Gascon, Guxens, & Sunyer, 2015; Talbott, Marshall et al, 2015), a number of classes of chemicals have been identified as potential contributors, including pesticides, phthalates, polychlorinated biphenyls (PCBs), solvents, air particulates (PM 2.5 ), traffic-related pollutants, ozone, and heavy metals, with the strongest evidence found for air pollutants and pesticides. Current findings are tempered by at least three issues—all of which suggest future directions for neurotoxicology research in the mental health arena.…”
Section: Broadening Outcome Measures In Neurotoxicology Researchmentioning
confidence: 99%
“…To date, we lack a clear understanding of the causes of ASD despite its serious social impact. Based on the most recent reviews of the role of environmental toxicants in the etiology of ASD (e.g., Rossignol, Genuis & Frye, 2014; Suades-González, Gascon, Guxens, & Sunyer, 2015; Talbott, Marshall et al, 2015), a number of classes of chemicals have been identified as potential contributors, including pesticides, phthalates, polychlorinated biphenyls (PCBs), solvents, air particulates (PM 2.5 ), traffic-related pollutants, ozone, and heavy metals, with the strongest evidence found for air pollutants and pesticides. Current findings are tempered by at least three issues—all of which suggest future directions for neurotoxicology research in the mental health arena.…”
Section: Broadening Outcome Measures In Neurotoxicology Researchmentioning
confidence: 99%
“…Air pollution is involved in cardiovascular disease [2], stroke [3] and respiratory diseases [4,5] such as lung cancer [6], childhood asthma [7] and atopic dermatitis [8]. Furthermore, perinatal exposure to polycyclic aromatic hydrocarbons (PAHs), nitrogen dioxide (NO 2 ) and particulate matter (PM) has been demonstrated to have a negative impact on neuropsychological development in children [9]. A study carried out in Sydney estimated that reducing particulate matter (PM2.5) by 10% for 10 years would avoid approximately 650 premature deaths [10].…”
Section: Introductionmentioning
confidence: 99%
“…The authors of a recent review identified polycyclic aromatic hydrocarbons (PAH), fine particulate matter with aerodynamic diameter ≤ 2.5 μm (PM 2.5 ), and nitrogen dioxides as air pollutants potentially harmful to neuropsychological development in children (Suades-Gonzalez et al 2015). Recent epidemiologic studies have examined whether air pollution exposure increases risk for adverse behavioral development including behaviors related to attention deficit hyperactivity disorder (ADHD).…”
Section: Introductionmentioning
confidence: 99%